ANALISIS KELAYAKAN HARGA JUAL DALAM PERSAINGAN PASAR PRODUK SYNTHETIC THICKENER - Putri, Dyah Puspitasari Sunaryo; Dewanti, Rully Nur (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to analyze the feasibility of the selling price of synthetic thickener products in tight market competition based on financial aspects of Net Present Value (NPV), Benefit Cost Ratio (BCR), and Profitability Index (PI) with three price levels from the price range requested by customers. The research was conducted using a qualitative research method with five stages, namely 1) defining the problem, 2) identifying each alternative, 3) analyzing the feasibility of the selling price with a three-level price scenario, 4) conducting a comparative analysis and 5) recommending the decision given. The results of the research with the NPV, PI and BCR methods are not feasible for price as well as level 1 and feasible for selling prices 2 and 3.